Complications following operative treatment of supination-adduction type II (AO/OTA 44A2.3) ankle fractures. Issue 6 (June 2020) - Carney, J.; Ton, A.; Alluri, R.K.; Grisdela, P.; Marecek, G.S.
Highlights: The overall complication rate for SAD (OTA/AO 44A2.3) type 2 ankle fractures is similar to that of the general ankle fracture population (13.8%). Our analysis did not identify any risk factors for complication following surgical treatment of SAD-2 fractures. Younger age and a direct medial approach were associated with superior functional outcome scores. Abstract: Introduction: There are few published studies that investigate the surgical treatment of supination-adduction (SAD, AO/OTA 44A2.3) ankle fractures. The purpose of this study was to describe the complications and outcomes following operative fixation of SAD type 2 ankle fractures. Materials and methods: We identified all SAD-2 ankle fractures that presented at our institution's two hospitals from 2006–2018. Demographics, operative data, and complications (deep infection, superficial infection, delayed union, failure of fixation, and unplanned reoperation) were recorded for all patients. Lastly, all included patients were contacted by telephone for the administration of an 8-question Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function (PF) and Pain Interference questionnaire (PI). Univariate and multivariate analysis was performed to identify risk factors for complication or poor functional outcome score. Results: 65 patients met inclusion criteria. The average time to surgery was 14 days and average follow-up was 20.5 (range: 0.4–60.9) weeks. There were 9 (13.8%) complications (4 deep infections, 3 superficial infections, 1 delayed union, 1 failure of fixation) and 6 unplanned reoperations. Univariate and multivariate analysis failed to identify any statistically significant risk factors for complication or reoperation. Eleven patients participated in the administration of PROMIS score questionnaires at a mean of 3.4 years postoperatively. The average PROMIS Physical Function T -score was 42.3 ± 11.3 and the average PROMIS Pain Interference T -score was 55.8 ± 7.8. Younger age was associated with a higher physical function score. The use of a direct medial approach to the medial malleolus was associated with a lower pain interference score. Conclusion: The overall complication rate for SAD (OTA/AO 44A2.3) type 2 ankle fractures is similar to that of the general ankle fracture population. We were unable to identify risk factors for complication or reoperation. Mean patient reported outcomes are within one standard deviation of the general population. Level of evidence: III, retrospective cohort study.